EQUITY VALUE ANALYSIS WITH THE INCOME APPROACH IN PALM OIL PLANTATION COMPANIES (CASE STUDY: PT SISIRAU AND PT SATYA AGUNG) - Sianipar, Alfred Johnson; Fachrudin, Khaira Amalia; Dwi Atmoko, Darmawan (Penerbit Lafadz Jaya, 2025)
Equity value is the net worth that belongs to the owners or shareholders of a company after all liabilities have been settled from the total assets owned. Equity value reflects the portion of net ownership in the company that truly belongs to the shareholders.This study aims to analyze the equity value of two palm oil plantation companies in Indonesia, PT Sisirau and PT Satya Agung, using an income-based approach through the Discounted Cash Flow (DCF) method. This approach is considered highly relevant for valuing companies with long-term income prospects and relatively stable cash flows, as is typical in the palm oil plantation industry. The study is also strategically significant, as both companies are preparing for an Initial Public Offering (IPO), where valuation becomes a key consideration for potential investors. The data used in this research consists of audited financial statements from 2017 to 2024 and financial projections for the period 2025 to 2034. The research applies a quantitative approach combined with descriptive analysis, using both primary and secondary data. Equity value is estimated based on projected Free Cash Flow to the Firm (FCFF), discounted using the Weighted Average Cost of Capital (WACC). The analysis also considers business risk, cost structure, CPO price trends, and relevant government regulations. The results indicate that the income approach provides a more accurate estimate of equity value, reflecting the future economic potential of the companies. PT Satya Agung has an indicative equity value of IDR 3.85 trillion, significantly higher than PT Sisirau's IDR 1.67 trillion. This difference is attributed to PT Satya Agung's stronger cash position, lower debt burden, and higher growth potential. Therefore, PT Satya Agung is considered more suitable to proceed with an IPO in the near future. This study concludes that the DCF is highly appropriate for valuing companies with long-term growth orientation and stable cash flow. Moreover, the findings contribute to academic literature and serve as a practical reference for companies, investors, regulators, and academics in understanding income-based equity valuation, particularly in the palm oil plantation sector.